Srategi Guru Akidah Akhlak dalam Membentuk Kecerdasan Spiritual Pada Siswa di Madrasah Aliyah Swasta - Ilham, Muhammad (Al-Miskawaih: Journal of Science Education, 2023)
This article discusses the strategy of aqidah moral teachers in forming spiritual intelligence in students at the Tanjung Private Madrasah Aliyah, Bathin VIII District. Based on qualitative research, data collection was carried out by observation, interviews and documentation. Data analysis was performed using domain analysis, taxonomic analysis and componential analysis. The research findings state that the teacher's strategy of aqidah morals in shaping students' spiritual intelligence is carried out by accustoming students to doing something good and right, and strengthening religious education and adding religious material to each class. Inhibiting factors faced by teachers include; student personality, the influence of the friendship environment, the influence of association outside of school, the lack of cooperation with student guardians, the lack of educational support facilities. Meanwhile, the teacher's efforts to overcome these obstacles include; increasing cooperation between schools and parents, establishing cooperation with students, and creating good conditions during the learning process. Artikel ini membahas tentang strategi guru akidah akhlak dalam membentuk kecerdasan spiritual pada siswa di Madrasah Aliyah Swasta Tanjung Kecamatan Bathin VIII. Berbasis pada penelitian kualitatif, pengumpulan data dilakukan secara observasi, wawancara dan dokumentasi. Analisis data dilakukan dengan menggunakan analisis domain, analisi taksonomi dan analisis komponensial. Temuan penelitian menyebutkan bahwa strategi guru akidah akhlak dalam membentuk kecerdasan spiritual siswa dilakukan dengan cara membiasakan peserta didik melakukan sesuatu yang baik dan benar, dan memperkuat pendidikan agama dan menambah materi agama disetiap kelas. Faktor penghambat yang dihadapi guru antara lain; pribadi peserta didik, pengaruh lingkungan pertemanan, pengaruh pergaulan diluar sekolah, kurangnya kerjasama dengan wali murid, kurangnya sarana penunjang pendidikan. Sedangkan upaya guru dalam mengatasi kendala tersebut antara lain; meningkatkan kerjasama antara sekolah dan orang tua, menjalin kerjasama dengan peserta didik, dan menciptakan kondisi yang baik di saat proses belajar berlangsung.